Recent results based on continuous GPS observations of the GIA process in Fennoscandia from BIFROST - Lidberg, Martin; Johansson, Jan M.; Scherneck, Hans-Georg; Milne, Glenn A. (Journal of Geodynamics, 2010)
International audience We present the latest 3D velocity field of the Fennoscandian Glacial Isostatic Adjustment (GIA) process from BIFROST. It is derived from more than 4800 days (13 years) of data at more than 80 permanent GPS sites. We use the GAMIT/GLOBK and the GIPSY/OASIS II software packages for GPS analysis and compare the results. The solution has an internal accuracy at the level of 0.2mm/yr (1 sigma) for horizontal velocities at the best sites. We also present a revised GIA prediction model. At the best sites, the optimal model agrees with the observations to within 0.4mm/yr. However, the model systematically overpredicts the magnitude of horizontal rates in the north. We discuss limitations in computed and presented GNSS station velocities, where especially possible instability over time causing non-linear pattern in vertical time series are considered. In extension, preliminary results from an investigation applying revised analysis strategies on a sparse subset of the data base are presented, indicating possible improvements for the future.